Martensitic twinning transformation mechanism in a metastable IVB element-based body-centered cubic high-entropy alloy with high strength and high work hardening rate. (10th October 2022) - Huang, Yuhe; Gao, Junheng; Vorontsov, Vassili; Guan, Dikai; Goodall, Russell; Dye, David; Wang, Shuize; Zhu, Qiang; Rainforth, W. Mark; Todd, Iain
Highlights: A high-entropy alloy with a high work hardening rate of 2–12.5 GPa and high tensile strength of 1.3 GPa was developed. The consistently high work hardening capability is realized by β→α" transformation, self-accommodation and mechanical twins. A new twinning transformation mechanism for the nucleation of a newly discovered 351 α" type I twinning is reported. Abstract: Realizing high work hardening and thus elevated strength–ductility synergy are prerequisites for the practical usage of body-centered-cubic high entropy alloys (BCC-HEAs). In this study, we report a novel dynamic strengthening mechanism, martensitic twinning transformation mechanism in a metastable refractory element-based BCC-HEA (TiZrHf)87 Ta13 (at.%) that can profoundly enhance the work hardening capability, leading to a large uniform ductility and high strength simultaneously. Different from conventional transformation induced plasticity (TRIP) and twinning induced plasticity (TWIP) strengthening mechanisms, the martensitic twinning transformation strengthening mechanism combines the best characteristics of both TRIP and TWIP strengthening mechanisms, which greatly alleviates the strength-ductility trade-off that ubiquitously observed in BCC structural alloys. Microstructure characterization, carried out using X-ray diffraction (XRD) and electron back-scatter diffraction (EBSD) shows that, upon straining, α" (orthorhombic) martensite transformation, self-accommodation (SA) α" twinning and mechanical α" twinning were activated sequentially. Transmission electron microscopy (TEM) analyses reveal that continuous twinning activation is inherited from nucleating mechanical 351α" type I twins within SA ''351''< 2 ¯ 11 >α" type II twinned α" variants on 351α" twinning plane by twinning transformation through simple shear, thereby accommodating the excessive plastic strain through the twinning shear while concurrently refining the grain structure. Consequently, consistent high work hardening rates of 2–12.5 GPa were achieved during the entire plastic deformation, leading to a high tensile strength of 1.3 GPa and uniform elongation of 24%. Alloy development guidelines for activating such martensitic twinning transformation strengthening mechanism were proposed, which could be important in developing new BCC-HEAs with optimal mechanical performance.